Examining the Predictors of Innovative Teaching Practices among Indonesian Lecturers - Mohamad Arief Rafsanjani; Albrian Fiky Prakoso; Eka Hendi Andriansyah; Purba Andy Wijaya; Andri Eko Prabowo; M. Rudi Irwansyah (Universidad Pedagógica Nacional, 2023)
Rapid developments in technology have changed the teaching and learning process. As a consequence, lecturers must innovate in their teaching practices to be effective and efficient. However, there is not enough literature that explains the key competencies for innovative teaching. Research mostly focuses on innovative teaching in general and theoretical perspectives. This article tries to explore the key predictors of innovative teaching practices. Structural equation modeling (SEM) was used to examine the research model on a sample of 274 teachers chosen at random. We used an online questionnaire to reach the participants who represent our population (Indonesian lecturers). The result indicates that four competencies (pedagogical, learning, technological, and social competency) significantly predict lecturers' innovative teaching performance. The findings provid important insight for those concerned with promoting innovative teaching skills among the Indonesian lecturers.